Profesionalisme, Kompetensi, Motivasi dan Pengaruhnya Terhadap Kinerja Auditor - Ayu Noorida Soerono; Iis Ismawati (Jurnal Riset Akuntansi Terpadu, 2020)
This study aims to determine the effect of professionalism, auditor competence, motivation, on auditor performance. The data used in this study are primary data with the selection of respondents based on purposive sampling method. Respondents in this study were 160 internal auditors of the Inspectorate in Banten Province. Respondents were selected based on the minimum S1 education criteria, had followed the functional auditor training program, and had at least 2 years work experience. Tests using multiple linear regression test. The results of this study indicate that professionalism, auditor competence, and motivation have a significant positive effect on auditor performance.